PRODUCTIVITY ENHANCEMENT OF SESAME (SESAMUM INDICUM L.) THROUGH IMPROVED PRODUCTION TECHNOLOGIES - SINGH, RUDRASEN; A. K. UPADHYAY,; SHRIVASTAVA, PRASHANT; V. K. SINGH,; S. K. SINGH, (The Bioscan, 2014)
The frontline demonstrations were conducted on 65 farmer’s fields of five adopted villages of Chhatarpur district in Bundelkhand region of Madhya Pradesh during kharif seasons of 2008 to 2012 in rainfed condition on light to medium soil with low to medium fertility status under sesame-gram cropping system to study the productivity enhancement of sesame through improved production technologies. The results revealed that the maximum average number of capsules per plant and number of seeds per capsule (103.62 and 71.10) were obtained under improved technology over to farmer’s practices (77.59 and 66.57) thus, there were 25.11 per cent more capsules per plant and 6.38 per cent seeds per capsule under improved technology as compared to local check. The maximum average test weight of sesame seeds (3.21 g) was recorded under improved technology over local check (2.70 g). The seed yields of sesame under improved technology ranged between 3.85 to 6.84 q ha-1 with average yield of 5.34 q ha-1 which was 34 per cent higher over the farmer’s practice (3.45 q ha-1). However, maximum average net returns (Rs.12914 ha-1) as well as benefit cost ratio (2.49) were recorded under improved technologies as compared to farmer’s practice (Rs.7740 ha-1 and 2.20).